Mapping Improvement of Community Empowerment in the village of Development - Sukaris, Sukaris; Pristyadi, Budiyono; Alkusani, Alkusani (Kontribusia : Research Dissemination for Community Development, 2019)
Community empowerment is Carried out in order to reduce poverty and unemployment, the which in turn will lead to an increase of in community welfare. However, the data-based empowerment programs have not been done much. So we need the first step in the success of community empowerment, it must start with understanding the community and its dynamics. The understanding needed is an understanding of the social and institutional arrangements of the community and an assessment is needed to design a good community development programs, and in accordance with the needs of the community so that the program can Achieve the right targets. The purpose of this coding program is to analyze the characteristics, potentials and problems of the village, analyze alternative empowerment programs for the targeted village communities and analyze and implement alternative programs for community empowerment activities. The approach used in resolving Reviews These services priority is the social mapping survey methods and the participatory rural appraisal (PRA) method, with the target of being Sambipondok Village communities and Manyar Sidorukun Village. The results show that both villages have dimension index in the lagging characteristics and developing indexes. The potentials of the two villages are Generally different, such as the potential for tourism villages and Also the potential for. with the target of being Sambipondok Village communities and Manyar Sidorukun Village. The results show that both villages have dimension index in the lagging characteristics and developing indexes. The potentials of the two villages are Generally different, such as the potential for tourism villages and Also the potential for. with the target of being Sambipondok Village communities and Manyar Sidorukun Village. The results show that both villages have dimension index in the lagging characteristics and developing indexes. The potentials of the two villages are Generally different, such as the potential for tourism villages and Also the potential for.